Palivizumab epitope–displaying virus-like particles protect rodents from RSV challenge - Schickli, Jeanne H.; Whitacre, David C.; Tang, Roderick S.; Kaur, Jasmine; Lawlor, Heather; Peters, Cory J.; Jones, Joyce E.; Peterson, Darrell L.; McCarthy, Michael P.; Van Nest, Gary; Milich, David R. (The Journal of clinical investigation, 2015)
Respiratory syncytial virus (RSV) is the most common cause of serious viral bronchiolitis in infants, young children, and the elderly. Currently, there is not an FDA-approved vaccine available for RSV, though the mAb palivizumab is licensed to reduce the incidence of RSV disease in premature or at-risk infants. The palivizumab epitope is a well-characterized, approximately 24-aa helix-loop-helix structure on the RSV fusion (F) protein (F254-277). Here, we genetically inserted this epitope and multiple site variants of this epitope within a versatile woodchuck hepadnavirus core-based virus-like particle (WHcAg-VLP) to generate hybrid VLPs that each bears 240 copies of the RSV epitope in a highly immunogenic arrayed format. A challenge of such an epitope-focused approach is that to be effective, the conformational F254-277 epitope must elicit antibodies that recognize the intact virus. A number of hybrid VLPs containing RSV F254-277 were recognized by palivizumab in vitro and elicited high-titer and protective neutralizing antibody in rodents. Together, the results from this proof-of-principle study suggest that the WHcAg-VLP technology may be an applicable approach to eliciting a response to other structural epitopes.